2019
DOI: 10.1016/j.ynstr.2019.100195
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal connectivity in the aftermath of acute social stress

Abstract: The hippocampus is a core brain region that responds to stress. Previous studies have found a dysconnectivity between hippocampus and other brain regions under acute and chronic stress. However, whether and how acute social stress influences the directed connectivity patterns from and to the hippocampus remains unclear. In this study, using a within-subject design and Granger causal analysis (GCA), we investigated the alterations of resting state effective connectivity from and to hippocampal subregions after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 126 publications
(165 reference statements)
0
22
1
Order By: Relevance
“…The hippocampus and insula are structurally and functionally connected, and their connectivity is associated with emotion processing, stress regulation, and mood disorders [90-92]. For example, acute social stress was shown to be associated with enhanced brain connectivity of the hippocampus-insula circuit in an experimentally induced social stress task [93]. Another study showed increased connectivity of the insula and hippocampus in association with the processing of untrustworthy faces [94].…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus and insula are structurally and functionally connected, and their connectivity is associated with emotion processing, stress regulation, and mood disorders [90-92]. For example, acute social stress was shown to be associated with enhanced brain connectivity of the hippocampus-insula circuit in an experimentally induced social stress task [93]. Another study showed increased connectivity of the insula and hippocampus in association with the processing of untrustworthy faces [94].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the greatest number of significantly correlated functional connections corresponded to the hubs of the DMN, such as the PHG, precuneus, and orbital gyrus (see Table 2 ). Previous studies have shown that DMN regional activity and connectivity between the DMN and other brain regions are associated with stress processes ( Boehringer et al, 2015 ; Chang and Yu, 2019 ; Dedovic et al, 2014 ; Hermans et al, 2014 ; Koric et al, 2012 ; Lederbogen et al, 2011 ; Maron-Katz et al, 2016 ; Quaedflieg et al, 2015a , b ; van Oort et al, 2017 ). Abnormal DMN connectivity was associated with stress-related psychopathologies, such as posttraumatic stress disorder (Bluhm et al, 2009; Rabinak et al, 2011) and depression (Greicius et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Early studies on the neural mechanism of PS identified the involvement of localized brain regions such as the limbic systems and prefrontal cortex ( Hermans et al, 2014 ; McEwen and Morrison, 2013 ; Menon, 2011 ; Pruessner et al, 2008 ; Seo et al, 2011 ; Sinha et al, 2004 ; Van Oort et al, 2017 ). Many studies have demonstrated that some limbic regions belonging to the default model network (DMN), such as the hippocampus and parahippocampus (PHG), are involved in stress processes ( Albert et al, 2015 ; Boehringer et al, 2015 ; Chang and Yu, 2019 ; Li et al, 2014 ; McEwen and Gianaros, 2011 ; Ploghaus et al, 2001 ; Sinha et al, 2004 ). Some regions of the salience network (SN), such as the amygdala, insula, and thalamus, that engage in detecting salient internal and external events are also important in stress-related processes ( Dedovic et al, 2014 ; Hermans et al, 2014 ; Li et al, 2014 ; Seo et al, 2011 ; Sinha et al, 2004 ; Wang et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, during decisions whether or not to engage in social interactions, higher levels of anxiety were found to be associated with increased functional connectivity between the right NAc and the amygdala, accompanied by decreased functional connectivity between the right NAc and the perigenual anterior cingulate cortex (pACC) [ 17 ]. Chang and Yu additionally highlight the importance of the thalamo-hippocampal-insular/midbrain circuit, where resting-state effective connectivity changed in response to the TSST [ 35 ]. Overall, there is limited evidence regarding the underlying neural substrates of social avoidance in healthy humans.…”
Section: Introductionmentioning
confidence: 99%